Surveillance of surgical site infection post vasectomy. Issue 1 (January 2013) - Nevill, Michael; Tanner, Judith; Robertson, David; Myers, Amanda; Lohr, Patricia A.
The aim of this study was to determine the incidence of surgical site infection (SSI) after vasectomy and to identify associated patient and perioperative risk factors, including the operating room environment (non-ventilated treatment room or ventilated operating theatre). This study used an active 30-day surveillance follow-up programme with telephone interviews and home visits. Patients were recruited over an 18 month period. Demographics, patient details and perioperative procedures were documented on the day of surgery. Patients were telephoned 10 and 30 days post procedure. Of 1, 155 patients enrolled, 994 (86%) completed the full 30-day follow-up. Of these, 25 (2.5%) developed an SSI. The mean number of days until presentation with an SSI was 13. No statistically significant difference was found in rates of SSI when vasectomies were undertaken in either ventilated operating theatres or non-ventilated treatment rooms.